Ultrasound measurements of abdominal muscle thickness are associated with postmenstrual age at full oral feedings in preterm infants: A preliminary study. (8th June 2021) - Nagel, Emily M.; Hickey, Marie; Teigen, Levi M.; Kuchnia, Adam; Schifsky, Holly; Holm, Tara; Earthman, Carrie P.; Demerath, Ellen; Ramel, Sara E.
Abstract: Background: A premature infant's discharge from the neonatal intensive care unit (NICU) is dependent on factors such as respiratory stability, adequate growth, and the ability to consume oral feeds. Once infants have achieved respiratory stability, a tool that can better predict age at discharge is desirable. Thus, we conducted a secondary data analysis to assess the association between ultrasound measurements of abdominal muscle thickness and postmenstrual age (PMA) at full oral feedings. Methods: Forty‐nine (n = 49) healthy, premature infants (mean gestational age = 32 weeks) were recruited from the NICU. Anthropometric measurements and ultrasound measurements of the rectus abdominis were conducted when infants were medically stable. Fat‐free mass (FFM) was obtained using air displacement plethysmography. The relationship between ultrasound measurements of muscle thickness and PMA at full oral feedings was assessed using linear regression analysis. The relationship between FFM z ‐scores and PMA at full oral feedings was also assessed for comparison. Results: When adjusting for gestational age at birth, PMA at measurement, days of positive pressure respiratory support, weight, and length, ultrasound measurements of abdominal muscle thickness were independently, negatively associated with PMA at full oral feedings (β estimate: −0.71, P = .03). Conclusion: Preliminary results suggest infants with greater abdominal muscle thickness may reach full oral feedings at an earlier PMA (nearly 1 week per millimeter). Thus, ultrasound measurements of abdominal muscle thickness may be helpful in assessing readiness for discharge in healthy preterm infants. Further research is needed for development and validation of a prediction equation.